A mechanistic investigation of an Iridium-catalyzed asymmetric hydrogenation of pyridinium salts. Issue 17 (26th April 2018) - Huang, Yuhua; Liu, Shaodong; Liu, Yizhou; Chen, Yonggang; Weisel, Mark; Williamson, R. Thomas; Davies, Ian W.; Zhang, Xumu
Abstract: NMR studies of the catalyst, deuteration experiments, mass spectrometry, and isolation and characterization of intermediates, allow us to propose an outer-sphere mechanism for the Iridium-catalyzed asymmetric hydrogenation of N -alkyl-2-arylpyridinium salts. Graphical abstract: